2004
DOI: 10.1063/1.1690297
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear model for magnetosonic shocklets in plasmas

Abstract: Exact nonlinear equations for magnetosonic shocklets in a uniform hot magnetoplasma are de-

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 6 publications
1
19
0
Order By: Relevance
“…First, in the past, many authors 5-7 discussed non-envelope soliton 5,6 and cnoidal wave 7 solutions of the CDA waves based on Eqs. 8 Third, ignoring the electron inertial effect, Shukla et al 9 examined the effect of finite b on the shock structures. Fourth, the combined influence of dispersion and dissipation on non-stationary CDA waves in a zerob plasma has been examined by Chakrabarti et al 10 Finally, when @ðB 2 þ 2blnnÞ=@x ¼ 0 in Eq.…”
mentioning
confidence: 99%
“…First, in the past, many authors 5-7 discussed non-envelope soliton 5,6 and cnoidal wave 7 solutions of the CDA waves based on Eqs. 8 Third, ignoring the electron inertial effect, Shukla et al 9 examined the effect of finite b on the shock structures. Fourth, the combined influence of dispersion and dissipation on non-stationary CDA waves in a zerob plasma has been examined by Chakrabarti et al 10 Finally, when @ðB 2 þ 2blnnÞ=@x ¼ 0 in Eq.…”
mentioning
confidence: 99%
“…It is in the fitness of the situation to mention here that Shukla et al (2004) studied the magnetosonic shocklets in 1-D and reported that steady state solutions could not be found in the absence of dispersion. However, in our case, the presence of dissipation reduces the equation to a form which is integrable and admits shock solutions even if the dispersion is absent.…”
Section: Derivation Of Cylindrical Kadomtsev-petviashvili-burgers (Ckmentioning
confidence: 78%
“…However, in our case, the presence of dissipation reduces the equation to a form which is integrable and admits shock solutions even if the dispersion is absent. It should, however, be noted that the equation was obtained in a different way by Shukla et al (2004). Note that the shock waves in the non-planar geometry differ significantly from its planar counterpart owing to the presence of ν/τ term in both Equations (17) and (19).…”
Section: Derivation Of Cylindrical Kadomtsev-petviashvili-burgers (Ckmentioning
confidence: 99%
See 1 more Smart Citation
“…Within the approximation (14), the first terms on the right-hand sides in Eqs. (18,19) can be neglected.…”
Section: Model and Equationsmentioning
confidence: 99%